Calculator search results

Formula
Solve the system of equations
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$x - \dfrac { y - 5 } { 2 } = 8$
$\dfrac { 5 } { 6 } x - \dfrac { y } { 4 } = \dfrac { 19 } { 4 }$
$x$-intercept
$\left ( \dfrac { 11 } { 2 } , 0 \right )$
$y$-intercept
$\left ( 0 , - 11 \right )$
$x$-intercept
$\left ( \dfrac { 57 } { 10 } , 0 \right )$
$y$-intercept
$\left ( 0 , - 19 \right )$
$\begin{cases} x- \dfrac{ y-5 }{ 2 } = 8 \\ \dfrac{ 5 }{ 6 } x- \dfrac{ y }{ 4 } = \dfrac{ 19 }{ 4 } \end{cases}$
$x = 6 , y = 1$
Solve quadratic equations using the square root
$\begin{cases} x - \dfrac { y - 5 } { 2 } = 8 \\ \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ x } - \dfrac { y } { 4 } = \dfrac { 19 } { 4 } \end{cases}$
$ $ Calculate the multiplication expression $ $
$\begin{cases} x - \dfrac { y - 5 } { 2 } = 8 \\ \color{#FF6800}{ \dfrac { 5 x } { 6 } } - \dfrac { y } { 4 } = \dfrac { 19 } { 4 } \end{cases}$
$\begin{cases} x - \dfrac { y - 5 } { 2 } = 8 \\ \dfrac { 5 x } { 6 } - \dfrac { y } { 4 } = \dfrac { 19 } { 4 } \end{cases}$
$ $ Solve a solution to $ x$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 11 } { 2 } } \\ \dfrac { 5 x } { 6 } - \dfrac { y } { 4 } = \dfrac { 19 } { 4 } \end{cases}$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 11 } { 2 } } \\ \color{#FF6800}{ \dfrac { 5 x } { 6 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { y } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } } \end{cases}$
$ $ Substitute the given $ x $ value into the equation $ \dfrac { 5 x } { 6 } - \dfrac { y } { 4 } = \dfrac { 19 } { 4 }$
$\color{#FF6800}{ \dfrac { 5 \left ( \dfrac { 1 } { 2 } y + \dfrac { 11 } { 2 } \right ) } { 6 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { y } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } }$
$\color{#FF6800}{ \dfrac { 5 \left ( \dfrac { 1 } { 2 } y + \dfrac { 11 } { 2 } \right ) } { 6 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { y } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } }$
$ $ Solve a solution to $ y$
$\color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$\color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$ $ Substitute the given $ y $ value into the equation $ x = \dfrac { 1 } { 2 } y + \dfrac { 11 } { 2 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 11 } { 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 11 } { 2 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
$ $ The possible solutions are as follows $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 6 } , \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ 6 } , \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$ $ Check if it is the solution to the system of equations $ $
$\begin{cases} \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 - 5 } { 2 } } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ \times } \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } } \end{cases}$
$\begin{cases} \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 - 5 } { 2 } } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ \times } \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } } \end{cases}$
$ $ Simplify the equality $ $
$\begin{cases} \color{#FF6800}{ 8 } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ \dfrac { 19 } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } } \end{cases}$
$\begin{cases} \color{#FF6800}{ 8 } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ \dfrac { 19 } { 4 } } = \color{#FF6800}{ \dfrac { 19 } { 4 } } \end{cases}$
$ $ Since it is true in both equations, it is the solution of the system of equations $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 6 } , \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$ $ 그래프 보기 $ $
Graph
Solution search results
search-thumbnail-$∩$ $∩1$ 
$ \begin{cases} 3\left(x-1\right)-2\left(1+x\right)<1 \\ 3x-11>0 \end{cases} $ $ \begin{cases} 3x-3-2+2x47 \\ 3x-4>0 \end{cases} $ 
$ \begin{cases} x<7+5 \\ 222l+4 \end{cases} $ $ \begin{cases} x<6 \\ 3x>4 \end{cases} $
1st-6th grade
Other
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo